Effect of topical corticosteroid application frequency on histamine-induced wheals - Narasimha, Sharma K.; Srinivas, C. R.; Mathew, Anil C. (International journal of dermatology, 2005)
Background  Very few studies have been conducted to assess the effect of corticosteroid application frequency to attain maximum benefit with minimum side‐effects. Objectives  Compare the efficacy of twice‐daily, once‐daily and alternate‐day applications of clobetasol propionate (0.05%) and compare whether an initial once‐daily application followed by a subsequent alternate‐day application is as effective as a once‐daily application. Methods  The ability of corticosteroids to suppress histamine‐induced wheals on human skin was used as a human bioassay model. Of the 26 subjects included, 21 completed the 1st phase. In the 2nd phase, 11 subjects were included and all completed the study. Four sites were chosen on the left forearm. Clobetasol propionate (0.05%) was applied twice daily, once daily, and on alternate days, and on the control site a color, texture and odour‐matched vehicle was applied. Prick test with histamine was carried out after 10 days. In the 2nd phase, clobetasol propionate (0.05%) was applied once daily for 14 days and compared with the initial once daily for 7 days and the subsequent alternate‐day application for 7 days. Prick test was carried out after 14 days. Results  The once‐daily application of clobetasol propionate (0.05%) was as effective as the twice‐daily application, but the alternate‐day application was less effective than the once‐daily application (P < 0.01). Also, the initial‐daily and subsequent alternate‐day applications were not as effective as the continuous once‐daily application (P < 0.05). Conclusion  A once‐daily application of clobetasol propionate (0.05%) is likely to provide the required therapeutic effect.